Optimization and characterisation of plant produced Human Papillomavirus pseudovirions in Nicotiana benthamiana - Adams, Ayesha (Department of Molecular and Cell Biology, 2020)
Human papillomavirus (HPV) is known to be the cause of anogenital and oropharyngeal cancers as well as genital and common warts. There are currently three prophylactic virus-like particle (VLP) based vaccines. These vaccines, however, do not offer protection against all HPV strains and cannot act therapeutically and so further vaccine development is still needed. The burden of HPV is also highest in low-income countries for which the vaccine costs are still quite high, and therefore alternative methods of vaccine production and testing are needed. HPV pseudovirions (PsVs) are synthetic viral particles that are made up of the L1 major and L2 minor HPV capsid proteins and encapsidate up to 8Kb of pseudogenome DNA without the need of an encapsidation signal. HPV PsVs are used to test neutralising antibodies elicited by vaccines, for studying the virus life cycle, and potentially for delivery of therapeutic DNA vaccines. HPV PsVs are typically produced in mammalian cells; however, it has recently been shown that HPV PsVs can be produced in plants, a potentially safer, cheaper and more easily scalable means of production. While, a current problem with plant HPV PsV production is low yields, research has shown that using pseudogenome DNAs between 5-7Kb increases yields of papillomavirus PsVs in mammalian cells. Therefore, the objective of this study was to determine the optimal pseudogenome size for encapsidation by plant produced PsVs, in order to increase the amount of PsVs in a sample as opposed to VLPs. Pseudogenome constructs encoding Enhanced Green Fluorescent Protein (EGFP )and ranging in size from 4.8Kb – 7.8kb were cloned into a geminivirus-derived replicating vector, transformed into Agrobacterium tumefaciens and then infiltrated into Nicotiana benthamiana along with plant expression vectors encoding the HPV 35 L1 and L2 capsid proteins. Particles were purified by iodixanol density gradient ultracentrifugation and the 27% and 33% fractions of this gradient analysed. Transmission electron microscopy (TEM) was used to confirm particle assembly and L1 expression was quantified by ELISA. Particles were disrupted with proteinase K and quantitative PCR was used to quantify the encapsidated DNA. Ratios of encapsidated DNA to L1 capsid protein were calculated for each of the PsV samples with different sized pseudogenomes, to account for batch-to-batch variation and as an approximation of which size pseudogenome is better encapsidated. Infective ability of the particles was analysed by incubating the PsVs onto HEK293TT cells and then checking for DNA delivery and protein expression by measuring EGFP expression by Western blots. The results showed that PsVs are found predominantly in the 27% fraction of the iodixanol gradient whereas the 33% fraction of the gradient appears to only contain VLPs. The data also indicated that the smaller pseudogenomes, were packaged more efficiently into PsVs as higher concentrations of encapsidated DNA and higher levels of EGFP expression were obtained when the 4.8Kb pseudogenome was used, compared to when the larger 5.8 - 7.8Kb pseudogenomes were used. Thus, the results showed that smaller pseudogenomes, around 4.8Kb, should be used for the plant production of HPV 35 PsVs as they are better packaged than larger pseudogenomes and thereby produce higher yields of functional PsVs.